INTEGRATING ICT TOOLS IN DEVELOPING READING STRATEGIES AMONG EFL LEARNERS - Khayrullayeva Dilorom Sayfutdinovna (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This study explores the role of information and communication technology (ICT) in enhancing reading strategies among English as a Foreign Language (EFL) learners. It highlights how integrating ICT tools—such as digital reading platforms, multimedia resources, and online applications—improves comprehension, motivation, and learner autonomy. The research employs a mixed-method design with experimental and control groups to examine differences in reading performance and strategy use. Results are expected to show that ICT-supported instruction fosters greater engagement and more effective application of cognitive and metacognitive strategies. The paper emphasizes that technology, when combined with pedagogical guidance, transforms traditional reading lessons into interactive, learner-centered experiences that align with 21st-century education. The findings offer practical implications for teachers, curriculum designers, and policymakers in developing innovative EFL reading programs.